Algerian Efforts to Enter the Information Society - sifoune, baya (Journal of Social Sciences and Humanities, 2016)
Perhaps the most significant results of the modern technological revolution are the radical changes that have occurred in the trajectory of societies, given what this revolution has produced in all aspects, particularly the intellectual and media dimensions. The use of these technologies has become an inevitable necessity to keep pace with the flow of life in all its facets within an information society that is developing at a staggering rate. Although the concept of the "Information Society" has not yet fully crystallized in the global thought of many researchers, there is a consensus that joining it is essential for all nations. Sound planning for entering the information society is a requirement for all countries aspiring to make this transition, as it must follow deliberate steps designed to achieve set programs. We observe that many developed countries are preparing programs to consolidate the information society and are taking numerous practical steps to realize them. If this is the situation of developed nations, what is the status of Algeria? What is required of it to achieve a successful entry into this society? And have the efforts made by the Algerian state to realize the information society borne fruit? Through these questions and others, this research paper attempts to evaluate Algeria's experience in entering the information society.